2022
DOI: 10.1021/acsomega.2c02198
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Analysis of Heavy Oil Viscosity Reduction by Ultrasound and Viscosity Reducers Based on Molecular Dynamics Simulation

Abstract: Ultrasound and viscosity reducers are commonly used methods to reduce the viscosity of heavy oil. In order to compare the viscosity reduction effects of ultrasound and viscosity reducers and study their mechanism of interaction on heavy oil, molecular dynamics simulation was carried out in this paper. First, a molecular model of heavy oil composed of asphaltene, resin, aromatic hydrocarbon, and saturated hydrocarbon was established in this work. Through molecular dynamics simulation, the different effects of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It is well-known that a small decrease in the content of the asphaltenes of oil can significantly reduce the viscosity of it. Even the changes in the molecular shape or conformation can alter the viscosity of heavy oil [41][42][43]. The results of viscosity measurements are illustrated in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that a small decrease in the content of the asphaltenes of oil can significantly reduce the viscosity of it. Even the changes in the molecular shape or conformation can alter the viscosity of heavy oil [41][42][43]. The results of viscosity measurements are illustrated in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the oil viscosity by SFU assisted extraction was significantly lower than that by the organic extraction. Within a certain period, the apparent viscosity of the oil was reduced by ultrasonic treatment [45] . This was because the greater the cavitation intensity, the more certain elements of oil were degraded by ultrasonic waves, resulting in a more significant decrement of apparent viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…In the MD simulation work of Xu et al, 24 it was revealed that the oil-soluble VRs induce the transformation from face-to-face stacking of asphaltenes to face-to-face stacking of asphaltenes and resins, which was considered as the mechanism of reducing heavy oil viscosity. Zhang et al 25 explored the effect of oil-soluble VRs along with ultrasound, demonstrating that the type and content of VRs influence the ultrasonic viscosity reduction effect.…”
Section: Introductionmentioning
confidence: 99%
“…To provide insights into microscopic interactions between different heavy oil components and VRs, which are difficult to obtain from experiments, computational methods including quantum mechanics (QM) calculations and molecular dynamics (MD) simulations have been employed to explore dynamics and thermodynamics in heavy oil systems. Based on this, the molecular mechanisms of water-soluble VRs ,, and oil-soluble VRs , have been studied. In the MD simulation work of Xu et al, it was revealed that the oil-soluble VRs induce the transformation from face-to-face stacking of asphaltenes to face-to-face stacking of asphaltenes and resins, which was considered as the mechanism of reducing heavy oil viscosity.…”
Section: Introductionmentioning
confidence: 99%